THE FIRST CENOZOIC OCTOPOD: A LOWER EOCENE RECORD FROM BOLCA, NORTHEASTERN ITALY (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2024)
To date, soft-tissue remains of extinct incirrate octopods have been described exclusively from UpperCretaceous deposits. Here, three specimens of an incirrate octopodid with well-preserved soft tissue imprints are described for the first time from Paleogene strata. This material originates from the upper Ypresian (lower Eocene) fish-bearing levels of the Bolca Konservat-Lagerstätte in the Pesciara of Bolca in north-eastern Italy. Previously, these specimens had tentatively been interpreted as teuthids. Based on a detailed study of their anatomical structure, a new genus and species of octopodid, Bolcaoctopus pesciaraensis, belonging to the extant family Octopodidae, are here erected. Bolcaoctopus gen. nov. may be distinguished from the Late Cretaceous genus Styletoctopus by the presence of long and thin arms and an elongated body shape with a narrowed apical end and covered by longitudinal wrinkles. Although finds of fossil octopuses in the Bolca Konservat-Lagerstätte remain extremely rare, it is worth noting that Cenozoic marine vertebrate localities constitute an important potential source of additional finds of coleoid cephalopods, the study of which may shed light on a poorly understood period in the evolutionary history of these molluscs.
Keywords: Cephalopoda; Coleoidea; Octopoda; Taxonomy; Paleogene; Bolca Konservat-Lagerstätte.